2018
DOI: 10.1155/2018/7862892
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Vitamin D Receptor Genes in Association with Childhood Autism Spectrum Disorder

Abstract: Both genetic and environmental factors have been implicated in the etiology of autism spectrum disorder (ASD). This case-control study aimed to determine the association of single-nucleotide polymorphisms (SNPs) rs731276 (TaqI), rs1568820 (Cdx2), rs1544410 (BsmI), and rs2228570 (FokI) in the vitamin D receptor (VDR) gene with susceptibility of childhood ASD and severity of the disease. A total of 201 children with ASD and 200 healthy controls from the Han Chinese population were recruited. SNP genotyping was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…The BsmI and Apa I polymorphisms located in intron 8 and TaqI are close to the 3'UTR region of the exon-9. The UTR region controls the VDR mRNA stability and post-transcriptional process which support the role of TaqI polymorphism in alteration of protein structure and vitamin D binding specificity [ 37 , 39 , 42 ].…”
Section: Reviewmentioning
confidence: 97%
See 3 more Smart Citations
“…The BsmI and Apa I polymorphisms located in intron 8 and TaqI are close to the 3'UTR region of the exon-9. The UTR region controls the VDR mRNA stability and post-transcriptional process which support the role of TaqI polymorphism in alteration of protein structure and vitamin D binding specificity [ 37 , 39 , 42 ].…”
Section: Reviewmentioning
confidence: 97%
“…The VDR is a member of the neurosteroid family which signifies the role of VDR as a candidate gene for ASD [ 36 - 38 ]. Studies showed the association of several single nucleotide polymorphisms (SNPs) of VDR genes with ASD but the SNPs could be variable for different population [ 39 ]. Three haplotypes of VDR is associated with ASD which are GTTT, GTCT, ATCG.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…While exposure to some factors (eg. outdoor air pollution) may be difficult to control, changes in nutrients intake are easier to implement, and are particularly important for ASD-subjects carrying known specific variants in genes like DHFR [125], MTHFR [126] and VDR [127].…”
Section: Gene-environment Interactions In Asdmentioning
confidence: 99%